Lithium experiment in tokamak T-11M and concept of limiter tokamak-reactor - Mirnov, S.V.; Azizov, E.A.; Alekseyev, A.G.; Gorbunov, Ya.V.; Vertkov, A.V.; Evtikhin, V.A.; Lazarev, V.B.; Lublinsky, I.E.; Prokhorov, D.Yu.; Sotnikov, S.M.; Tugarinov, S.N. (Вопросы атомной науки и техники, 2006)
The paper suggests the addition or replacement of the magnetic divertor by lithium limiter as producer of irradiated blanket, which should prevent tokamak first wall and divertor plates from local high power loads. The main physical basis of this idea is lithium localization close plasma boundary and poor penetration into plasma center in process of its puffing, as was shown in tokamak experiments. The mushroom tokamak lithium limiter with capillary porous system (CPS) can be used for this aim. The hot part of this limiter can work as lithium emitter to tokamak plasma and cold parts can work as collectors of lithium flowing out of the plasma column. The surface capillary forces of limiter CPS will return the collected liquid lithium from cold to hot parts of limiter again and close the lithium circulation "limiterplasma-limiter".